2005
DOI: 10.1038/ni1294
|View full text |Cite
|
Sign up to set email alerts
|

Association of β-arrestin and TRAF6 negatively regulates Toll-like receptor–interleukin 1 receptor signaling

Abstract: Tumor necrosis factor receptor-associated factor 6 (TRAF6) is critical for mediating Toll-like receptor (TLR)-interleukin 1 receptor (IL-1R) signaling and subsequent activation of NF-kappaB and AP-1, transcriptional activators of innate immunity. Here we show that beta-arrestins, a family of multifunctional proteins, directly interacted with TRAF6 after TLR-IL-1R activation. Formation of the beta-arrestin-TRAF6 complex prevented autoubiquitination of TRAF6 and activation of NF-kappaB and AP-1. Endotoxin-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
225
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(249 citation statements)
references
References 42 publications
19
225
5
Order By: Relevance
“…NMDA activation-induced dendrite spine remodeling in neurons is dependent on the scaffolding protein ␤-arrestin-2 (24). This was of interest because ␤-arrestin-2 is known to modulate LPS-induced inflammatory responses, but its role in inflammasome activation is not known (5,22,25,33). Our results clearly show that aspartate-dependent downregulation of inflammasome function in vitro and in vivo is dependent on ␤-arrestin-2.…”
Section: G735supporting
confidence: 52%
“…NMDA activation-induced dendrite spine remodeling in neurons is dependent on the scaffolding protein ␤-arrestin-2 (24). This was of interest because ␤-arrestin-2 is known to modulate LPS-induced inflammatory responses, but its role in inflammasome activation is not known (5,22,25,33). Our results clearly show that aspartate-dependent downregulation of inflammasome function in vitro and in vivo is dependent on ␤-arrestin-2.…”
Section: G735supporting
confidence: 52%
“…In vitro experiments have shown that TRAFs become polyubiquitinated in a Ubc13-dependent manner upon ligation of TNFRs and TLRs (7,22). To determine whether Ubc13 is required for the polyubiquitination of TRAF6 in vivo, we immunoprecipitated TRAF6 from spleen lysates prepared from LPS-treated ubc13 ϩ/Ϫ and ubc13 ϩ/ϩ mice and then analyzed the immunoprecipitated proteins by immunoblotting with antiubiquitin antibody.…”
Section: Ubc13 ؉/؊ Mice Are Born Normally and Exhibit No Abnormalitiementioning
confidence: 99%
“…Replicationdeficient adenoviruses encoding GFP-tagged full-length of ␤-arrestin-2 (Arrb2-GFP adenovirus), GFP-tagged ␤-galactosidase (gal-GFP adenovirus), and HA-tagged ␤-arrestin-2 mutant with deletion of its N-terminal (Arrb2-ND-GFP adenovirus) were prepared as before (6,48). The titers of these three adenoviruses were about 1.0 ϫ 10 11 PFU/mL.…”
Section: Microinjection and Expression Of Recombinant Adenovirus In Lamentioning
confidence: 99%
“…␤-arrestin-2 negatively regulates CXCR2-mediated neutrophil chemotaxis (4) and plays a role in allergic-asthmatic inflammation (5). The interaction of ␤-arrestin-2 with TRAF6 negatively modulates Toll-like receptor signaling in innate immunity (6). ␤-arrestin-1 functions as a positive regulator for CD4 ϩ T cell survival and autoimmunity (7).…”
mentioning
confidence: 99%